Plithogenic Iadov model to study university teaching practices in the complexity of the educational process of comprehensive training by competencies - Pedro Barrientos Gutiérrez; Katia Ninozca Flores-Ledesma; Santos Lucio Guanilo Gómez; Jorge Luis López Bulnes; Jorge Leonardo Jave Nakayo; Carlos Francisco Cabrera Carranza; Abrahan Cesar Neri Ayala; Santiago Ernesto Ramos Yovera (Neutrosophic Sets and Systems, 2023)
Teaching practices constitute a dynamic performance with the capacity for transformation, the evolution of human consciousness, autonomy, leadership and conscious commitment to strategic intervention with a holistic vision in the process of teaching and educating that generates emotionally healthy spaces to “learn to learn”, to do, to coexist, to be and to undertake the student. In this context, the article reports research that had the purpose of measuring and modeling the meanings of university teaching practices in the complexity of the educational process of comprehensive competency training. To do this, 25 professors from Latin American universities were surveyed regarding the impact of today's university graduates in the region on social life, technology, and entrepreneurship. The plithogenic Iadov technique was introduced to process the data, where the Iadov logic chart becomes mainly Plithogenic Inconsistent Picture Fuzzy Numbers. We consider that the theory of plithogeny makes a formal approach to complex phenomena because it generalizes dynamic systems.